Local Government Accounting System’s Effect on Malang City Financial Statements Quality - Sandita, Genoveva Trifila; Setiyono, Benediktus Rifaldo; Dhey, Falentina Chinuriga; Dopo, Rita Stefania Anu (Journal of Transformative Governance and Social Justice, 2024)
This article discusses the impact of the local government accounting system’s implementation on the quality of financial management reports in the Malang City Government. The research employs a case study method, gathering data through interviews, observations, and document analysis. These methods are used to examine the implementation of local government accounting systems and the quality of financial statements. The study’s primary objective is to demonstrate that the local government accounting system’s implementation significantly influences the quality of the Malang City Government’s financial management reports. The findings suggest that the accounting system’s effective implementation can enhance the quality of financial reporting, thereby promoting transparency and accountability in local government operations. During the implementation process, local governments must consider crucial aspects such as system planning, system implementation, and system evaluation. System planning involves defining the system’s objectives, identifying the necessary resources, and developing a detailed plan for system implementation. System implementation refers to the process of putting the plan into action, while system evaluation involves assessing the system’s performance against the defined objectives. Moreover, the study emphasizes the importance of involving all relevant stakeholders in the implementation of the local government accounting system. Stakeholder involvement can ensure that the system meets the needs of all parties and can contribute to the system’s success. In conclusion, the research underscores the significant role of the local government accounting system in enhancing the quality of financial management reports in the Malang City Government. It also highlights the need for careful planning, effective implementation, ongoing evaluation, and stakeholder involvement in the system’s implementation. The research method used is a case study with a qualitative approach, providing in-depth insights into the subject matter.